Phenethyl isothiocyanate and dasatinib combination synergistically reduces hepatocellular carcinoma growth via cell cycle arrest and oxeiptosis - Strusi, Gabriele; Suelzu, Caterina M.; Horwood, Nicole; Münsterberg, Andrea E.; Bao, Yongping (Frontiers in Pharmacology, 2023)
Hepatocellular carcinoma (HCC) is the most common type of liver cancer which is among the most lethal tumours. Combination therapy exploits multiple drugs to target key pathways synergistically to reduce tumour growth. Isothiocyanates have been shown to possess anticancer potential and to complement the anticancer activity of other compounds. This study aimed to investigate the potential of phenethyl isothiocyanate (PEITC) to synergise with dasatinib, improving its anticancer potential in HCC. MTT and clonogenic assays were used to assess the combination anti-tumour effect in vitro, whereas a murine syngeneic model was employed to evaluate the combination efficacy in vivo. Flow cytometry and Western blot assays were used to elucidate the molecular mechanism. PEITC and dasatinib combination exhibited a synergistic effect in vitro and in vivo. The combination induced DNA damage and oxidative stress through the production of reactive oxygen species (ROS), which led to the formation of a premature CDK1/Cyclin B1 complex associated with induction of mitotic catastrophe. Furthermore, ROS activated oxeiptosis, a caspase-independent form of cell death. PEITC can enhance dasatinib action in treating HCC with ROS-induced cell cycle arrest and oxeiptosis. This highlights the role that ITCs may have in cancer therapy as a complement of clinically approved chemotherapeutic drugs.